Experience of Social Interaction of a Future Specialist as a Unified Basis for Continuous Education - Gubarenko, Irina V. (2020)
The implementation of the competency-based approach in a multi-level education system has posed the problem of continuity of its levels. The search for common grounds in choosing the content and results of education has intensified. The scientific interest in the student’s experience has grown, as the basic basis for the formation of competencies. Experience is an extremely general category in the scientific apparatus of many sciences, such as philosophy, sociology, psychology, pedagogy, and understanding of its essential properties determines the choice of the content of education. Increasingly, the experience of human behavior in a changing society is becoming the subject of research by educators. Educational standards for training specialists in the sociogenic sphere contain a capacious block of social competencies formed in the educational process at the meta-subject and subject levels. The difficulty of ensuring the systemic integrity of the content of education, which includes individual, disparate elements of activity reflected in the social competencies of a future specialist, determines the theoretical and experimental search for an effective educational construct that maximally covers the content of these competencies and the ways of its formation. The genesis of the concept of social interaction indicates the progressive movement of scientific ideas from a socially insignificant and little studied phenomenon to its dominant role in the formation and development of social reality. In most psychological and pedagogical concepts, experience is considered as a passive result of activity, which determines its static structure. The dynamic structure of the experience of social interaction is formed by the value-semantic, thought-activity and expressive-activity components. Subjectivity, co-existence, and reflexivity are proposed as the through lines of its enrichment for all levels of education. The results of the study can serve as a theoretical basis for designing the enrichment of the experience of social interaction of students at different levels of education.